2020
DOI: 10.1177/2049463720917182
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous intradiscal injection of radiopaque gelified ethanol: short- and long-term functional outcome and complication rate in a consecutive series of patients with lumbar disc herniation

Abstract: Lumbar disc herniation (LDH) is a common cause of low back pain (LBP) and/or radicular pain (RP). Over the years, different therapies have been proposed to treat symptomatic LDH, including different minimally invasive techniques and open surgical methods. Recently, percutaneous intradiscal injection of radiopaque gelified ethanol (RGE) DiscoGel® has emerged as an effective therapeutic option in patients with LDH. Nevertheless, only few studies addressed the reliability of this technique. The purpose of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…The preliminary results have rekindled the interest in chemonucleolysis, which was abandoned about the turn of the century. In the ensuing years, several studies corroborated the ethanol gel efficacy in the treatment of radicular pain, sciatica, and disc hernias [ 28 , 29 , 30 , 31 , 32 ]. We are aware of only two papers on GEI in patients with lumbar DP [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary results have rekindled the interest in chemonucleolysis, which was abandoned about the turn of the century. In the ensuing years, several studies corroborated the ethanol gel efficacy in the treatment of radicular pain, sciatica, and disc hernias [ 28 , 29 , 30 , 31 , 32 ]. We are aware of only two papers on GEI in patients with lumbar DP [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol gel is easy to handle, and the presence of radiopaque tungsten facilitates injection monitoring. Several studies demonstrated the efficacy and safety of gelified ethanol injection (GEI) [ 28 , 29 , 30 , 31 , 32 ]. Please note that in the literature this procedure is also referred to as ethanol gel chemonucleolysis.…”
Section: Introductionmentioning
confidence: 99%
“…La Torre et al 20 demonstrated DiscoGel efficacy in a retrospective cohort, showing a reduction in VAS pain from 8.4 ± 1.04 to 2.8 ± 1.07 ( P < 0.05) and an increase in Short Form-36 from 27.2 ± 12.21 to 74.3 ± 13.31 ( P < 0.05) at 1-month follow-up that was sustained at a final mean follow-up of 44 months. At final follow-up, 92.5% of patients had VAS improvement >50%, with only four patients requiring open surgery for persistent severe pain.…”
Section: Nonbiologic Therapiesmentioning
confidence: 99%
“…DiscoGel is a sterile viscous solution composed of gelified ethanol in a tungsten particle suspension. 20 The solution is injected into the NP to fill radial fissures with new gelatinous material. The hypothetical mechanisms of action are reducing intradiscal pressure by osmotic dehydration of the nucleus, resulting in decompression of the offended nerve roots as well as denaturation of nociceptive nerve endings in the degenerated disk.…”
Section: Intradiscal Injectablesmentioning
confidence: 99%
See 1 more Smart Citation